ENKRIPSI CITRA WARNA MENGGUNAKAN RUBIK’S CUBE DAN THREE CHAOTIC LOGISTIC MAP - Ronsen Purba; Frans Agus Purba; Sari Fatmawati (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2016)
An image encryption is a technique to protect the image secrecy from illegal accessing. One of the encryption algorithm that are used is Rubik's Cube where this algorithm used to permute the pixel in the color image. However, the key used in the Rubik's Cube is not random so the security of image is still weak. To further improve the security of the image, then used the chaotic systems for generating random keys. Excess of chaos is the sensitivity to initial conditions, behave randomly and do not have a recurring period. One of the chaos function used is Three Chaotic Logistic Maps where necessary keys generated are used in encryption and decryption proceses. The test results show that the algorithm Rubik's Cube and Three Chaotic Logistic Maps on the encryption and decryption processes do not cause an error in the original image and the result image. Neighboring pixels have a low coefficient indicating that the quality of the results encryption is good and resistant toward to attack by adding noise. The nature of chaotic sensitivity cause cipher image will not be recovered if the keys used in decryption are slightly diffrent from the encryption keys. that the decrypted image does not revert to plain image so the image obtained more secure.